Can Riots be Democratic? On the Fight for Recognition via Violent Means - Højme, Philip (Itinerari, 2023)
This essay seeks to examine D’Arcy’s notion of sound militancy to discern whether this term can be fruitfully applied to establishing rioting (riots) as a democratic form of resistance to injustice or negligence. The first part of the essay provides an account of Frazer and Hutchings’ critique of political violence, a critique that perceives violence (used in politics or for political aims) as never being justifiable. In opposition to this position, the second part of the essay posits, through both theoretical (Marcuse, Celikates) and practical (Soei, Sutterlüty) references, the case for an understanding of political violence (riots) as justifiable or defensible in certain circumstances – those that adhere to D’Arcy’s concept of sound militancy and seek to address a particular and present grievance. In conclusion, the essay suggests that (Hegelian) recognition provides an account of why marginalizing seems so pervasive in contemporary Western societies.